Strategic Integration of Real Options for Enhanced Valuation and Optimization in Mining Project Planning under Uncertainty: A Comprehensive Review - Ali, Maaz A.; Rafique, Quasir (International Journal of Project Management, 2024)
Purpose: In the contemporary landscape of mining projects, the imperative to navigate through periods of uncertainty has driven the exploration of alternative strategic tools rooted in project flexibility. Real options have emerged as a pivotal strategic approach, offering the means to adapt and refine mining projects under unpredictable conditions Materials and Methods: This paper provides a comprehensive review and discussion on the strategic application of real options for optimizing mining project planning in the face of uncertainty. Organized into four sections, the paper begins with a general introduction to real options in Section one, delving into their strategic and technical classifications. Section two critically examines and reviews the indispensable role of real options in the realms of mining investment and project planning. The third section is dedicated to an in-depth discussion of the strategic tools inherent in real options, specifically focusing on their valuation and optimization aspects within mining project planning. The final section provides a discussion and conclusion on the strategic application of real options for optimizing mining project planning under uncertainty. Findings: The review identifies that real options offer valuable strategic flexibility in addressing uncertainties inherent in mining project planning. Through a detailed examination of their application, it becomes evident that real options can enhance decision-making processes and improve project outcomes by allowing for adaptive responses to changing conditions. Implications to Theory, Practice, and Policy: The strategic integration of real options into mining project planning presents significant implications for theory, practice, and policy. Theoretical implications include advancing understanding of decision-making under uncertainty and the role of flexibility in strategic planning. In practice, the adoption of real options can lead to improved project outcomes, increased resilience to market fluctuations, and enhanced risk management strategies. From a policy perspective, recognizing the value of real options may inform regulatory frameworks and promote the adoption of flexible planning approaches within the mining industry, ultimately contributing to sustainable development and resource management.